Pediatrician's cough and cold medication prescription for hypothetical cases - A cross-sectional multi-centric study - Sudha Chandelia; Mukesh Dhankar; Meetu Salhan (Elsevier, 2016)
Background: Concerns over inappropriate use of cough and cold medication (CCM) in children have been raised. In addition to being ineffective, these are now considered toxic for young children. Despite this fact studies from some regions have shown high use of these medications by physicians. However data on pediatricians and from India are negligible. Aim: To study the burden and patterns of cough and cold medications use by pediatricians for hypothetical cases. Methods: In this cross-sectional study; 172 pediatricians of various hospitals of Delhi and Haryana were enrolled from February 15 to March 15, 2012. They were contacted personally by authors and asked to write their prescriptions for two hypothetical case scenarios [having cough and cold] of two different age groups; (1) less than 2 years and (2) 2-5 years. We made two categories as recommendations exist for children less than 2 years while recommendations for the second category are underway. Results were summarized as percentages, counts and; presented in tables and figures. Chi square test was used to establish association between categorical variables of subgroups. Results: Response rate was 93%. The most used CCM was antihistaminics (82%) and systemic sympathomimetics (48%). The use of CCM was significantly less in teaching hospitals as compared to non-teaching (77% vs. 95%; p-value - 0.025). However there was no statistical difference in the practice of post graduates and more senior pediatricians (p value-0.895). No difference in CCM use in two age groups {(82% (less than 2 years) vs. 85% (2-5 years); p-value - 0.531} was observed. Conclusion: Overall use of CCM is still high irrespective of patient age, pediatrician's seniority or hospital setting. Efforts should be made to create awareness among the pediatricians regarding cautious use of these medications.